The Menemukan Makna Esensi dan Eksistensi Hidup di Tengah Fenomena Bunuh Diri di Indonesia Jean Paul Sartre: Finding the Meaning of the Essence and Existence of Life Amidst the Suicide Phenomenon in Indonesia Jean Paul Sartre - Emanuel, Yohanes; Adon, Mathias Jebaru (Undiksha, 2025)
This paper focuses on the analysis of suicide as a form of individual inability to understand the essence and existence of themselves in the world. The increasing phenomenon of suicide in various age groups lately shows various motives, but the main problem is often not only the pressure of life, but the loss of understanding of the essence and existence of oneself. This ignorance makes individuals vulnerable to choosing to end their lives when facing problems. Therefore, an in-depth study of this phenomenon is needed. In this paper, the author focuses on two main questions: why are those who do not understand their essence and existence more likely to choose suicide when facing problems? and how can someone find their essence and existence in the world when faced with difficult life problems? In studying this problem, the author uses a literature study method by referring to articles, documents and various journals and related books. Hopefully, this article can help readers to find the essence and existence of themselves in the world, so that when faced with a problem they do not immediately choose to end their lives as a way out to solve the problem. Life is basically a gift given by the Creator and should not be removed by force for any reason.